2009
DOI: 10.1038/ajg.2008.159
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Chronic Hepatitis B Virus Infection Among Taiwanese Human Immunodeficiency Virus Type 1–Positive Persons in the Era of Nationwide Hepatitis B Vaccination

Abstract: Our study showed a significant decline of seroprevalence of HBV infection among both HIV-negative and -positive persons who were born in the era of the nationwide HBV vaccination in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 36 publications
2
29
2
Order By: Relevance
“…In Taiwan, the prevalence of chronic HBV infection is estimated to be 15 to 20% among individuals born before the implementation of a nationwide HBV vaccination program in 1984. In contrast to what has been observed in Western countries, we have found that the HBV seroprevalence among injecting drug users (IDU) is similar to that of other groups at risk for HIV transmission (32). Between 2003 and 2006, an outbreak of HIV infection and hepatitis C virus (HCV) infection occurred among IDU who shared needles and diluent in Taiwan (4,7).…”
contrasting
confidence: 40%
“…In Taiwan, the prevalence of chronic HBV infection is estimated to be 15 to 20% among individuals born before the implementation of a nationwide HBV vaccination program in 1984. In contrast to what has been observed in Western countries, we have found that the HBV seroprevalence among injecting drug users (IDU) is similar to that of other groups at risk for HIV transmission (32). Between 2003 and 2006, an outbreak of HIV infection and hepatitis C virus (HCV) infection occurred among IDU who shared needles and diluent in Taiwan (4,7).…”
contrasting
confidence: 40%
“…In our previous study, the seroprevalence of HBsAg and anti-HBc was compared between HIV-positive and HIV-negative persons born before 1984. 17 Compared with HIV-negative persons born before July 1984, HIV-positive persons born before July 1984 had a significantly higher seroprevalence of HBsAg (20.3% vs. 15.5%, p < 0.001) and anti-HBc (78.9% vs. 72.1%, p < 0.001). 17 In addition, a significant decline in HBV seroprevalence among both HIV-negative and -positive persons born in the era of the nationwide HBV vaccination in Taiwan has also been shown.…”
Section: Discussionmentioning
confidence: 96%
“…17 Compared with HIV-negative persons born before July 1984, HIV-positive persons born before July 1984 had a significantly higher seroprevalence of HBsAg (20.3% vs. 15.5%, p < 0.001) and anti-HBc (78.9% vs. 72.1%, p < 0.001). 17 In addition, a significant decline in HBV seroprevalence among both HIV-negative and -positive persons born in the era of the nationwide HBV vaccination in Taiwan has also been shown. 17 In this study, positive antiHBs status alone, which indicates the prevalence of HBV vaccination-related protection, among HIV-negative and -positive MSM were 67.1% and 68.6%, respectively.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations